2018
DOI: 10.1016/j.bbr.2017.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recovery of traumatic brain injury-induced functional deficits is not hindered by daily administration of lorazepam

Abstract: Agitation and aggression are common sequelae of traumatic brain injury (TBI) and pose a challenge to physicians and other health providers during acute patient care and subsequent neurorehabilitation. Antipsychotic drugs (APDs) are routinely administered to manage TBI patients displaying such maladaptive behaviors despite several clinical and preclinical studies demonstrating that they hinder recovery. A potentially viable alternative to APDs may be the benzodiazepines, which have differing mechanisms of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“… 42 , 70 , 71 Benzodiazepines, which have differing mechanisms of action, may also be a viable alternate approach for managing agitation given that Cheng and colleagues showed that lorazepam provided for 19 days after CCI injury improved motor and cognitive outcome. 72 An intensive care unit trial demonstrated that non-D 2 -antagonist alternative medications, such as alpha-2 agonist dexmedetomidine, outperformed HAL in reducing post-TBI agitation and delirium with lower adverse event rates. 73 …”
Section: Discussionmentioning
confidence: 99%
“… 42 , 70 , 71 Benzodiazepines, which have differing mechanisms of action, may also be a viable alternate approach for managing agitation given that Cheng and colleagues showed that lorazepam provided for 19 days after CCI injury improved motor and cognitive outcome. 72 An intensive care unit trial demonstrated that non-D 2 -antagonist alternative medications, such as alpha-2 agonist dexmedetomidine, outperformed HAL in reducing post-TBI agitation and delirium with lower adverse event rates. 73 …”
Section: Discussionmentioning
confidence: 99%
“…They can delay neurobehavioral recovery, neuroplasticity, and repair post TBI (Arciniegas & Silver, 2006;Rao, Jellinek & Woolston, 1985). However, a recent study evaluating the effects of lorazepam after experimental TBI in rats showed that intermittent use of lorazepam may have an effect in improving agitation and aggression in TBI without affecting functional recovery (Cheng et al, 2018). As a general guideline, avoid medications that can worsen cognition including potent dopamine blockers (typical antipsychotics, drugs with potent D2 blocking properties like risperidone) and medications with anticholinergic side effects (paroxetine).…”
Section: Literature Review Of Pharmacological Managementmentioning
confidence: 99%